2022
DOI: 10.1152/ajpcell.00417.2021
|View full text |Cite
|
Sign up to set email alerts
|

UBR5 is a novel regulator of WNK1 stability

Abstract: The with no lysine (K) 1 (WNK1) protein kinase maintains cellular ion homeostasis in many tissues through actions on ion cotransporters and channels. Increased accumulation of WNK1 protein leads to pseudohypoaldosteronism type II (PHAII), a form of familial hypertension. WNK1 can be degraded via its adaptor-dependent recruitment to the Cullin3-RBX1 E3 ligase complex by the ubiquitin-proteasome system. Disruption of this process also leads to disease. To determine if this is the primary mechanism of WNK1 turnov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 82 publications
0
2
0
Order By: Relevance
“…This is supported by the finding that WNK1 abundance was increased and OSR1/SPAK activation were observed in mice lacking NEDD4-2 ( Roy et al, 2015 ; Al-Qusairi et al, 2017 ). We recently showed that WNK1 is degraded not only by the ubiquitin-proteasome pathway, but also by the lysosomal pathway ( Jung et al, 2022 ). Non-lysosomal cysteine proteases calpain and caspase-3 were also able to influence WNK1 abundance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is supported by the finding that WNK1 abundance was increased and OSR1/SPAK activation were observed in mice lacking NEDD4-2 ( Roy et al, 2015 ; Al-Qusairi et al, 2017 ). We recently showed that WNK1 is degraded not only by the ubiquitin-proteasome pathway, but also by the lysosomal pathway ( Jung et al, 2022 ). Non-lysosomal cysteine proteases calpain and caspase-3 were also able to influence WNK1 abundance.…”
Section: Introductionmentioning
confidence: 99%
“…Non-lysosomal cysteine proteases calpain and caspase-3 were also able to influence WNK1 abundance. This study identified UBR5 (ubiquitin protein ligase E3 component N-recognin 5) as a previously unknown regulator of WNK1 turnover that mediates lysosomal degradation of WNK1 protein ( Jung et al, 2022 ). Though UBR5 inhibition only modestly elevated WNK1 protein, that change caused a significant increase in phosphorylation of OSR1/SPAK, indicating that even small changes in WNK1 protein will have a significant impact on cellular processes.…”
Section: Introductionmentioning
confidence: 99%